Biochemical Evaluation of Groundwater of Karond Area of Bhopal, India - Kataria, H.C.; Pandey, Subhash; Singh, Arun (Asian Journal of Chemistry, 2016)
Biochemical analysis of groundwater (bore-well) of Karond area of Bhopal city has been studies in winter, summer and monsoon season for one year 2003–04. Two readings have been observed in one season for preliminary analysis of water quality index. Temperature, pH, electrical conductivity, free CO2, chloride, total alkalinity, total hardness, Ca-hardness, Mg-hardness were reported in the range of 21–320, 6.4–7.6, 282–680 μmhos/cm, 6.00–36.0, 78–128.4 ppm, 118.6–248, 58.0–104.8, 36–74 and 14.2–32.8 ppm, respectively. While DO, BOD, COD, NO3– and SO42– range from 1.12–1.64, 2.00–3.2, 20.4–78.6, 3.6–11.2 and 32–70.2 ppm. MPN count index were noted in the range of 6.00–980.0 at different sampling stations.